POLA REPRODUKSI BURUNG TEKUKUR (Streptopelia chinensis) DAN PUTER (Streptopelia risoria) DI PENANGKARAN (Reproductive Pattern of Spotted Dove (Streptopelia chinensis) and Ringdove (Streptopelia risoria) in Captivity) - Burhanuddin Masyud (Media Konservasi, 2007)
This study was carried out to know reproductive pattern of spotted dove (Streptopelia chinensis) and ringdove (Streptopelia risoria) in captivity. Fifteen pairs of spotted dove and seventeen pairs of ringdove were used to identify reproductive pattern. Each pairs of the birds were cared in cage (1.5 x 0.75 x 2.0 m). Result of this research showed that both types of the birds had the same pattern of reproduction, i.e : age of puberty (first mating) or onset of first egg production was 6.5 -7 months, avarage clutch size was two eggs, hatching period was 14.47 ± 0.74 days, egg production period was 27.11 ± 6.72 days to 48.79 ± 3.53 days, and hatching rate was 55% to 68%. The length of sperm head was 13.00 ± 0.62 μm to 14.73 ± 0.46 μm and the width of sperm head was 1.00 μm and the length of sperm tail was 87.00 ± 9.59 μm to 104.00 ± 6.22 μm. Sperm motility and concentration were relatively the same i.e 50 – 60% and 270 x 106 to 710 x 106 respectively. The birds were identified as temporal monogamous mating type.Key words: Streptopelia chinensis, Streptopelia risoria, reproductive pattern, matting type, captivity.